What's Wrong with Computer-Generated Images of Perfection in Advertising? - Spurgin, Earl W. (Journal of business ethics, 2003)
Advertisers often use computers to create fantastic images. Generally, these are perfectly harmless images that are used for comic or dramatic effect. Sometimes, however, they are problematic human images that I call computer-generated images of perfection. Advertisers create these images by using computer technology to remove unwanted traits from models or to generate entire human bodies. They are images that portray ideal human beauty, bodies, or looks. In this paper, I argue that the use of such images is unethical. I begin by explaining the common objections against advertising and by demonstrating how critics might argue that those objections apply to computer-generated images of perfection. Along the way, I demonstrate an ethically significant difference between computer-generated images of perfection and the images in ordinary ads. I argue that although critics might use this fact to apply the common objections to the use of computer-generated images of perfection, the objections fail. Finally, I argue that despite surviving the common objections, the use of computer-generated images of perfection is subject to an ethical objection that is based on aesthetic considerations. Advertisers are ethically obligated to avoid certain aesthetic results that are produced by computer-generated images of perfection.